Association of relative fat mass with asthma: inflammatory markers as potential mediators - Meicen Zhou; Ting Zhang; Ziyi Zeng; Shuqin Zeng; Shaopu Wang; Hua Wang (Lipids in Health and Disease)
Abstract Background This study aimed to investigate the association between relative fat mass (RFM) and asthma, as well as to explore the mediating role of Systemic Immune-Inflammation Index (SII) and Systemic Inflammation Response Index (SIRI). Methods This cross-sectional study utilized data from the National Health and Nutrition Examination Survey from 2007 to 2018. Associations between RFM and asthma were tested using multivariable logistic regressions, restricted cubic splines, subgroup analyses, and interaction tests, with mediation analysis for SII and SIRI. The inflection point was determined by the two-piecewise linear regression. Sensitivity analysis and propensity score matching (PSM) was applied to validate the stability of the associations. Results Higher RFM was positively associated with asthma, with an inflection point at 34.08. Below this threshold, each unit increase in RFM was positively associated with a 2% increase in the odds of asthma (Odds ratio (OR) 1.02, 95% Confidence interval (CI): 1.00—1.03), while above it, the association strengthened, with a 5% increase in the odds per unit (OR 1.05, 95% CI: 1.04—1.07). The association was consistent across subgroups. The association between RFM and asthma is stronger in current asthma patients than in ever had asthma ones. Mediation analyses showed that SII and SIRI partially mediated 7.48% and 3.88% of the RFM-asthma association, respectively. The findings remained robust after sensitivity analyses and adjusting for confounding bias using PSM. Conclusions RFM is positively associated with the prevalence of asthma in the U.S., particularly among individuals with current asthma, with systemic inflammation partially mediating this relationship.